Children’s Education teachers remembering their childhoods: the danger of the idealization of being a child (Olhar de Professor, 2020)
The purpose of this article is to analyze the views of six teachers of Early Childhood Education in the municipal network of Imperatriz/MA on childhood and children in contemporary times, using their oral narratives as a source. A biographical investigation is carried out, using Narrative Interviews with six teachers, as a device for data production, which were analyzed based on the proposal by Fritz Schütze (2011). Their narratives reveal their experiences as a child and show much of what they think about childhood, showing signs of what it is for them to be a child in contemporary times. Knowing the life trajectories of teachers is essential for those who work as a trainer in teacher training courses, as it is about, among many things, enabling the demystification of an ideal childhood, of a child model, allowing them to (re) think about what it is to be a child in contemporary times so as not to fall into the false idea of ​​idealization.
Keywords: Teaching narratives. Teachers of Early Childhood Education. Childhood.